Bioluminescent probe for detecting endogenous hypochlorite in living mice. Issue 4 (5th January 2018) - Tang, Chunchao; Gao, Yuqi; Liu, Tingting; Lin, Yuxing; Zhang, Xiaomeng; Zhang, Chaochao; Li, Xiang; Zhang, Tianchao; Du, Lupei; Li, Minyong
Abstract : As a kind of biologically important reactive oxygen species (ROS), hypochlorite (ClO − ) plays a crucial role in many physiological processes. Abstract : As a kind of biologically important reactive oxygen species (ROS), hypochlorite (ClO − ) plays a crucial role in many physiological processes. As such, endogenous ClO − is a powerful antibacterial agent during pathogen invasion. Nonetheless, excessive endogenous ClO − could pose a health threat to mammalian animals including humans. However, the detection of endogenous ClO − by bioluminescence probes in vivo remains a considerable challenge. Herein, based on a caged strategy, we developed a turn-on bioluminescent probe 1 for the highly selective detection of ClO − in vitro and imaging endogenous ClO − in a mouse inflammation model. We anticipate that such a probe could help us understand the role of endogenous ClO − in a variety of physiological and pathological processes.